THE EFFECTIVENESS OF PHYSICS TEACHING MATERIALS ON THE THEME OF â€œGLOBAL WARMING SYMPTOMSâ€ BASED ON SCIENTIFIC LITERACY TO INCREASE THE STUDENTSâ€™ COGNITIVE ABILITIES - purwiyantini, yeni; Rusilowati, Ani; Astuti, Budi (Universitas Negeri Semarang, 2019)
The purpose of this research is to develop teaching materials based on scientific literacy with categories of scientific literacy that isbalanced, feasible to use, easy to understand, and improve students? cognitive ability. The study used pre-test and post-test control group design. Based on the results of the research, the ratio of the content of scientific literacy in the teaching materials developed with the ratio of 40%: 20%: 20%: 20%. Teaching materials are considered feasible to use with an average score of 91.67% eligibility score and legibility with an average score of 89.47%. The improvement of scientific literacy ability of students using scientific-based literacy materials was 0,51 while the students who used teaching materials circulating in school was 0,26. In the experimental class had increased of cognitive learning outcomes and the average of affective and psychomotor learning outcomes were higher than control class. This shows the literacy-based materials science material symptom of Global Warmingcould improve the ability of scientific literacy.